Bibliometric study on the knowledge graph of immunotherapy for head and neck cancer - Wang, Ji; Gong, Zhengpeng; Yu, Ming (Frontiers in Oncology, 2023)
Background Head and neck squamous cell carcinoma (HNSCC) is a common malignant tumor with a significant mortality rate, especially in patients at locally advanced stage, or with recurrence and metastasis. Immunotherapy has shown remarkable breakthrough in the treatment of locally advanced cancer, recurrence and metastasis in recent years. During this time, a large number of HNSCC immunotherapy studies have been published. However, few studies employed bibliometric analysis. This work analyzes HNSCC immunotherapy trends and hotspots using bibliometric analysis to get better understanding of the current state and future direction of HNSCC immunotherapy. Methods Relevant articles and publications about immunotherapy of HNSCC were extracted from Web of Science Core Collection (WoSCC). Bibliometrics was used to study these publications in terms of countries/regions, institutions, authors (cited authors), journals (cited journals), references, and keywords, so as to identify research hotspots and to predict future research trends in this field. Results A total of 1377 English articles published between 2000 and 2022 were collected. It is found that the number of articles increases rapidly from 2016. The United States has the largest number of publications (n=538), followed by China (n=407) and Germany (n=175). The institute with the highest published papers is the University of Pittsburgh (n=67). In terms of author, Robert L Ferris ranks first among the top ten cited authors. Oral Oncology (impact factor (IF) (2021) = 5.972) is the most prolific academic journal in immunotherapy of HNSCC. According to the reference cluster analysis, the research hot topic has shifted from basic research on immunotherapy of head and neck cancer to the study of prognosis. Keywords analysis also reveals that the study of patients’ prognoses is at the core of immunotherapy for HNSCC. Conclusion Currently, head and neck cancer research focus primarily on prognostic significance, cancer treatment, and poor prognosis. However, the researches on immunotherapy for head and neck malignancies is the growing trend in near future. Notably, United States has made significant contributions to this field.